A Contribution to Comparative Theology: Probing the Depth of Islamic Thought - Khorchide, Mouhanad (Religions, 2013)
Muslim theologians, as much as ordinary Muslims, will immediately agree with the characterization of God as all compassionate. However, it remains rather opaque how God’s compassion can be fully explained in terms of comparative theology. How can Muslims relate to God’s compassion? What role does God’s compassion precisely play in the Quranic revelation and the daily practice of Muslims?